High-Throughput Quantitative Intrinsic Thiol Reactivity Evaluation Using a Fluorescence-Based Competitive Endpoint Assay. (October 2017) - Sameshima, Tomoya; Miyahisa, Ikuo; Yamasaki, Seiji; Gotou, Mika; Kobayashi, Toshitake; Sakamoto, Junichi
In a high-throughput screening (HTS) process, the chemical reactivity of test samples should be carefully examined because such reactive compounds may lead to false-positive results and adverse effects in vivo. Among all natural amino acids, the thiol side chain in cysteine has the highest nucleophilicity; thus, assessment of intrinsic thiol group reactivity in the HTS processes is expected to accelerate drug discovery. In general, k chem (M −1 s −1 ), the secondary reaction rate constant of a compound to thiol, can be evaluated via time course measurements of thiol-compound adducts using liquid chromatography–mass spectroscopy; this requires time-consuming and labor-intensive procedures. To overcome this issue, we developed a fluorescence-based competitive endpoint assay that allows quantitative calculation of the reaction rate of test compounds in an HTS format. Our assay is based on the competitive reaction for a free thiol (e.g., glutathione) between the test compounds and a fluorescent probe, o -maleimide BODIPY. Our assay provides robust data with a satisfactory throughput at an affordable cost. Our k chem evaluation method has advantages over previous assays in terms of higher throughput and quantitativeness. Thus, it contributes to early elimination of reactive compounds as well as quantitative evaluation of the k chem values of covalent inhibitors.